An analysis of revenue collection in Capricorn District Hospitals in Limpopo from 2001-2006 - Mabyana, Ruth Sebolaishi (My University, 2007)
The Department of Health and Social Development in Limpopo endeavors to efficiently and effectively manage revenue collection. The study analyzed the revenue collection for the Capricorn district hospitals from 2001 to 2006 by identifying problems and possible solutions related to revenue collection. A quantitative analysis of data has been obtained from in- depth structured interviews and revenue records. An analytic retrospective study design was used. All revenue records from 2001/2002 to 2006/2007, financial managers, revenue clerks, and clients /patients who came to request credit from each hospital constituted the population of the study. The findings were that in 2001/2002 none of the hospitals were able to attain the revenue targets. In 2005/2006 revenue targets were increased by almost double the amount however all hospitals were able to attain the revenue targets as prescribed. It implies that the hospitals were able to collect more revenue than in the previous financial year. It has been noted that the appointment of CEOs has brought a tremendous change in revenue collection. It has been identified that revenue is the life blood for a country or institution. The institutions need commitment of all stakeholders to collect revenue.
Thesis (MBA.) -- University of Limpopo, 2007
Keywords: Revenue collection; Public finances; Revenue; Local finance -- South Africa; Tax collection; Taxation